Variations in DNA methylation and the role of regulatory factors in rice (Oryza sativa) response to lunar orbit stressors - Du, Xiaohui; Zhang, Yan; Zhang, Meng; Sun, Yeqing (Frontiers in Plant Science, 2024)
Deep space flight imposes higher levels of damage on biological organisms; however, its specific effects on rice remain unclear. To investigate the variations in DNA methylation under deep space flight conditions, this study examined rice seeds carried by Chang’e-5. After 23 days of lunar orbital flight, the samples were planted in an artificial climate chamber and subjected to transcriptome and DNA methylation sequencing during the tillering and heading stages. The methylation patterns in the rice genome exhibited variability in response to lunar orbital stressors. DNA methylation alters the expression and interaction patterns of functional genes, involving biological processes such as metabolism and defense. Furthermore, we employed single-sample analysis methods to assess the gene expression and interaction patterns of different rice individuals. The genes exhibiting changes at the transcriptional and methylation levels varied among the different plants; however, these genes regulate consistent biological functions, primarily emphasizing metabolic processes. Finally, through single-sample analysis, we identified a set of miRNAs induced by lunar orbital stressors that potentially target DNA methylation regulatory factors. The findings of this study broaden the understanding of space biological effects and lay a foundation for further exploration of the mechanisms by which deep space flight impacts plants.